Adolf Hitler: Historical Figure and The Psychology Of Power (Eurasian Scientific Herald, 2025)
This article analyzes the personality of Adolf Hitler, one of the most significant and simultaneously controversial historical figures of the 20th century, his pursuit of power, and the political activities he carried out through it, based on a historical-political and psychological approach. Hitler's mental state, family environment, school experiences, and social interactions, shaped from childhood, are examined as the primary factors influencing his political worldview. Additionally, the article evaluates his oratory skills, ideological propaganda, activities within the Nazi party, and role in establishing a totalitarian regime. Throughout the article, the complex interplay between psychopathic traits in Hitler's personality, leadership ambitions, and historical circumstances is explored. The analysis is conducted using modern theories of political psychology and historical sources.